Diphtheria Disease and Genes Involved in Formation of Diphthamide, Key Effector of the Diphtheria Toxin - Uthman, Shanow; Liu, Shihui; Giorgini, Flaviano; Stark, Michael J.R.; Costanzo, Michael; Schaffrath, Raffael (IntechOpen, 2012)
None